Підстави припинення поруки за законодавством України - Федосеев, П. M.; Федосеев, П. Н.; Fedoseev, P. (Одеса : Юрид. л-ра, 2012)
Article is devoted to topical issues of termin tion bail by t h e laws of Ukraine , not e d a p a r t i c u l a r c o n t r a c t t e r m , t h e possibility of obtaining additional g u a r a n t e e s of obligations u n d e r t h e main c o n t r a c t , t h e definition of t h e t e r m of t h e obligation, a n d t h e definition of p a r t i e s to such obligation.
Федосеев П. М. Підстави припинення поруки за законодавством України / П. М. Федосеев // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 448-453.
Keywords: інститут поруки; зобов ' язання; термін; припинення строку; умови договору; институт поручительства; обязательства; срок; истечение срока; условия договора; Institute bail; obligation; term; terminatin of the term of the contract terms